The Higher Education Teacher and the New Challenges of Teaching in the Context of Digital Technologies: A Socio-Cognitive Approach [O Professor Do Ensino Superior E Os Novos Desafios Da Docência No Contexto Das Tecnologias Digitais: Uma Abordagem Sociocognitiva] [Le Professeur de L’Enseignement Supérieur Face Aux Nouveaux Enjeux de L’Enseignement Dans Le Contexte Des Technologies Numériques: Une Approche Socio-Cognitive] - Bezerra-Ferreira, J (Centro de Estudos Sociais da Universidade de Coimbra, 2022)
This article aims to analyze the metaphorical meanings that higher education teachers have attributed to digital technologies in the context of the COVID-19 pandemic. Our qualitative research is a phenomenological study using reports produced by faculty members from nine public universities in the North/Northeast of Brazil on the Google Forms platform as an instrument for the generation of data. The study assumes a socio-cognitive view of language, focused on the theoretical contribution of Cognitive Linguistics, with a conceptual metaphor approach, directed at corpus and discourse. Using the target-domain method to identify metaphors based on the corpus, those with a negative nature, such as exclusion and despair, stand out more frequently. © 2022 Centro de Estudos Sociais da Universidade de Coimbra. All rights reserved.
Keywords: Brazil; digital technologies; higher education; metaphor; teaching; university education